Somatic genome editing with the RCAS-TVA-CRISPR-Cas9 system for precision tumor modeling - Oldrini, Barbara (Nat Commun, 2018)
To accurately recapitulate the heterogeneity of human diseases, animal models require to recreate multiple complex genetic alterations. Here, we combine the RCAS-TVA system with the CRISPR-Cas9 genome editing tools for precise modeling of human tumors. We show that somatic deletion in neural stem cells of a variety of known tumor suppressor genes (Trp53, Cdkn2a, and Pten) leads to high-grade glioma formation. Moreover, by simultaneous delivery of pairs of guide RNAs we generate different gene fusions with oncogenic potential, either by chromosomal deletion (Bcan-Ntrk1) or by chromosomal translocation (Myb-Qk). Lastly, using homology-directed-repair, we also produce tumors carrying the homologous mutation to human BRAF V600E, frequently identified in a variety of tumors, including different types of gliomas. In summary, we have developed an extremely versatile mouse model for in vivo somatic genome editing, that will elicit the generation of more accurate cancer models particularly appropriate for pre-clinical testing.